TINJAUAN YURIDIS TERHADAP BENDA BERGERAK YANG DIJAMINKAN PADA BANK MANDIRI DI KOTA SAMARINDA TANPA MELALUI PROSES PENDAFTARAN FIDUSIA - Nada Yulianti (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACT Confidence to the bank that loans given to customers can be accepted again in accordance with the terms agreed upon together and that also to minimize the risks contained and always possible to arise in every loan release. Fiduciary guarantees have long been used in Indonesia. Legal protection for creditors in credit agreements with fiduciary guarantees is very necessary, considering that objects that are the object of fiduciary collateral are on the debtor so that if the debtor defaults on credit agreements with fiduciary collateral, the creditor's interests can be guaranteed with these legal protections. Legal protection for these creditors is regulated in general, namely: regulated in the Civil Code Article 1131 and 1132 and Law No.42 of 1999 concerning Fiduciary Guarantees basically states that objects burdened with fiduciary guarantees must be registered and then made a fiduciary guarantee certificate. The creditor has the right to carry out as stated in the fiduciary guarantee certificate if the debtor defaults. The results show that in practice fraud often occurs when registering fiduciary guarantees by irresponsible individuals or financial institutions themselves. From the results of this study, it can be concluded that in entering into a credit agreement with fiduciary collateral if the object guaranteed in the bank turns out not to go through the fiduciary registration process, the creditor does not have an executorial right as a result of not registering the fiduciary guarantee agreement and there must be a decision from the District Court. If the execution continues before the court ruling, the execution is said to be illegal.Keywords: Object, Banks, Fiduciary guarantee